2007
DOI: 10.1097/01.pcc.0000270837.66217.3b
|View full text |Cite
|
Sign up to set email alerts
|

The use of repeated head computed tomography in blunt pediatric head trauma: Factors predicting new and worsening brain injury*

Abstract: Repeat head computed tomography imaging is frequently used. About 30% of repeated computed tomographies showed new or worsening brain injury. However, worsening brain injury on repeat computed tomography rarely resulted in neurosurgical intervention. Patients with moderate or severe head injury and intraparenchymal injuries were more likely to show worsening brain injury and undergo neurosurgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 35 publications
3
77
2
2
Order By: Relevance
“…These large studies suggest that repeat imaging studies in the early timeframe are rarely beneficial in the absence of clinical deterioration. 1,9,12,20,21 Our study of outpatient imaging is in agreement with this principle, as no patients without clinical deterioration required intervention.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…These large studies suggest that repeat imaging studies in the early timeframe are rarely beneficial in the absence of clinical deterioration. 1,9,12,20,21 Our study of outpatient imaging is in agreement with this principle, as no patients without clinical deterioration required intervention.…”
Section: Discussionsupporting
confidence: 68%
“…Nonetheless, these studies did find that neurosurgical interventions in hospitalized TBI patients are typically based on clinical changes in most circumstances. Hollingworth et al 9 retrospectively evaluated children admitted to their trauma center over a 9-year period and found that early repeat CT-within 24 hours-was frequently worse in patients at a rate of 30%. Worsened imaging, however, rarely resulted in neurosurgical intervention without associated clinical worsening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabori et al [27] and Hollingworth et al [28 ] each noted 1 EDH patient with changed management after a second repeat scan, but these patients also had clinical deterioration. These observations highlight the need for a better understanding of the utility of multiple repeat CT scans in clinically stable EDH patients so that CT imaging may be optimally used to direct treatment while minimizing radiation exposure and its associated risks [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In the first stage, imputation models were specified for predictors and for mortality at six months, considering other fullyobserved covariates (such as age and GCS score). In the second stage, for each of the previously imputed datasets, imputation models were specified for the Extended Glasgow Outcome Scale for those patients who were either known to be alive at six months or were predicted to be alive by the first stage imputation model, considering fully-observed covariates and intermediate endpoints [28,59] 30 [21,45] Male, n .8) 1116 (20.5) [2800]…”
Section: Handling Of Missing Datamentioning
confidence: 99%